2017
DOI: 10.11113/mjfas.v0n0.590
|View full text |Cite
|
Sign up to set email alerts
|

Boundary layer flow of mixed convection viscoelastic micropolar fluid over a horizontal circular cylinder with aligned magnetohydrodynamic effect

Abstract: The boundary layer flow of a viscoelastic micropolar fluid over a horizontal circular cylinder with aligned magnetohydrodynamic effect is considered. The governing boundary layer equations are transformed into non-dimensional form by using appropriate dimensionless variables. The non-dimensional governing equations are then transformed into similarity equations and solved using an implicit finite difference scheme known as the Keller box method. Numerical results on the distributions of velocity and temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The present model constituted of governing equations and appropriate boundary conditions for Jeffrey fluid and dust particle respectively. Prior to undertaking the numerical solutions, they are transformed to the ordinary differential equations ( 11)- (15). The numerical method of Runge-Kutta Fehlberg (RKF45) is one of the more practical approaches to adopt for this problem in which the computation is set up in the Maple software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present model constituted of governing equations and appropriate boundary conditions for Jeffrey fluid and dust particle respectively. Prior to undertaking the numerical solutions, they are transformed to the ordinary differential equations ( 11)- (15). The numerical method of Runge-Kutta Fehlberg (RKF45) is one of the more practical approaches to adopt for this problem in which the computation is set up in the Maple software.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, combining different types of fluid in the flow field creates another class of fluid model, provided that these fluids need to be compatible with each other. Recently, a number of studies have proposed Jeffrey fluid and viscoelastic fluid being incorporated with micropolar fluid for the case of aligned magnetic field flow [14,15]. In line with this case, however, it has been suggested for the dusty Casson fluid as in two-phase flow model and the solutions are obtained numerically for both Casson fluid and solid particles [16].…”
Section: Introductionmentioning
confidence: 99%
“…Both studies have demonstrated that magnetic effect does exist on the flow. The study of magneto-convective viscoelastic micropolar has been discussed by Aziz et al, [20] but this study will put more focus on the flow itself in terms of the velocity and boundary layer separation without consideration of the heat transfer process.…”
Section: Introductionmentioning
confidence: 99%
“…Anwar et al, [13] examined the flow in viscoelastic fluid at constant temperature, whereas Ishak et al, [14] found the dual solutions in flow of micropolar fluid. Moreover, Aziz et al, [15] studied the flow of viscoelastic micropolar fluid flow with the effect of magneto-hydrodynamic. Later on, Aziz et al, [16] concentrated on the development model of viscoelastic fluid with the influence of microrotation.…”
Section: Introductionmentioning
confidence: 99%